SELECTIVITI OF GILL NET FISHING GEAR IN PONGKAI VILLAGE ISTIQOMAH SUBDISTRICT XII KOTO KAMPAR DISTRICT KAMPAR PROVINSI RIAU - Syafriadi, Rio; Nofrizal, Nofrizal; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Experimental fishing was conducted to test effectively the selectivity of gill nets in pongkai istiqomah village. Two mesh sizes (1.75 and 1.5 inches) were set randomly and operated on the river to evaluate the size of the most dominant fish caught. The results show that the highest fish catch is a 1.75 inch net as 43 heads, while the 1.5 inches net is 29 individuals.The net catch on the number and size of gill net catches is discussed in this paper completly. Keywords: fishing catches, gill net, catch